1990
DOI: 10.1128/iai.58.8.2621-2627.1990
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of an interleukin-1-like factor in human gingival crevicular fluid from patients with chronic inflammatory periodontal disease

Abstract: A significant level of interleukin-l-(IL-1)-like activity was detected in gingival crevicular fluid obtained from sites in patients with chronic inflammatory periodontal disease, confirming a previous report of IL-i-like activity detected in human gingival crevicular fluid from patients with chronic inflammatory periodontitis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…In contrast, anti IL-1b did not affect the stimulatory effect of GCF. These findings are in agreement with studies demonstrating that stimulation of thymocyte proliferation by GCF can be inhibited by anti IL-1a , but not by anti IL-1b (Kabashima et al 1990, Matsuki et al 1993, and that assesments of IL-1a and b in GCF, using ELISA, showed that IL-1a is the predominant form (Masada et al 1990). IL-1ra is a peptide with sequence homology to both IL-1a and b, that specifically blocks the action of IL-1 at the level of the IL-1 receptor (Dinarello 1991).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, anti IL-1b did not affect the stimulatory effect of GCF. These findings are in agreement with studies demonstrating that stimulation of thymocyte proliferation by GCF can be inhibited by anti IL-1a , but not by anti IL-1b (Kabashima et al 1990, Matsuki et al 1993, and that assesments of IL-1a and b in GCF, using ELISA, showed that IL-1a is the predominant form (Masada et al 1990). IL-1ra is a peptide with sequence homology to both IL-1a and b, that specifically blocks the action of IL-1 at the level of the IL-1 receptor (Dinarello 1991).…”
Section: Discussionsupporting
confidence: 92%
“…The fact that IL-1, on a molar basis, is the most potent stimulator of bone resorption in organ culture (Dewhirst et al 1983), together with reports demonstrating the presence of IL-1 in GCF (Masada et al 1990, Kabashima et al 1990, Matsuki et al 1993, Preiss & Meyle 1994, suggest the possibility that IL-1 may be responsible for the bone resorbing activity in GCF. This view is further supported by our observations that the main bone resorbing activity with a molecular weight of 3000-30,000 Dalton (i) is sensitive to temperature inhibition and (ii) causes enhanced production of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…When concentrations of IL-la and IL-ip in GCF were measured using an ELISA kit specific for these cytokines, seven samples of GCF from moderate inflammation sites in patients with periodontitis predominantly consisted of IL-ia. as previously reported (4). In one site in patient P-5 [P-5-(ii)], who suffered severe inflammation before receiving periodontal treatment including scaling, root planing, and flap surgery, the IL-ip level in the GCF was elevated drastically, in contrast to the undetected level in GCF from a moderate inflammation site.…”
Section: Patients and Concentrations Of Il-1 In Gingivai Crevicuiar Fsupporting
confidence: 69%
“…Severe inflammation had GI=3 and complaints of spontaneous pain. Preparation of GCF was carried out as previously described (4). As a negative control, we obtained GCF samples from healthy volunteers without periodontal disease.…”
Section: Human Subjectsmentioning
confidence: 99%
“…26 IL-1 has been detected in gingival biopsies and in the GCF of periodontal patients. [27][28][29][30][31] Cross-sectional studies have also shown increased GCF IL-1 levels in sites with periodontitis compared to healthy sites, 30 and at sites with experimental gingivitis. 32 Minocycline HCl is a tetracycline derivative that is active against a broad spectrum of Gram-negative and Gram-positive anaerobes including organisms implicated in chronic periodontitis.…”
mentioning
confidence: 98%